16th International Congress on Antiphospholipid Antibodies Task Force Report on Antiphospholipid Syndrome Treatment Trends. (October 2020) - Cohen, Hannah; Cuadrado, Maria J; Erkan, Doruk; Duarte-Garcia, Ali; Isenberg, David A; Knight, Jason S; Ortel, Thomas L; Rahman, Anisur; Salmon, Jane E; Tektonidou, Maria G; Williams, David J; Willis, Rohan; et al.
Antiphospholipid syndrome (APS), an acquired autoimmune thrombophilia, is characterised by thrombosis and/or pregnancy morbidity in association with persistent antiphospholipid antibodies. The 16th International Congress on Antiphospholipid Antibodies Task Force on APS Treatment Trends reviewed the current status with regard to existing and novel treatment trends for APS, which is the focus of this Task Force report. The report addresses current treatments and developments since the last report, on the use of direct oral anticoagulants in patients with APS, antiplatelet agents, adjunctive therapies (hydroxychloroquine, statins and vitamin D), targeted treatment including rituximab, belimumab, and anti-TNF agents, complement inhibition and drugs based on peptides of beta-2-glycoprotein I. In addition, the report summarises potential new players, including coenzyme Q10, adenosine receptor agonists and adenosine potentiation. In each case, the report provides recommendations for clinicians, based on the current state of the art, and suggests a clinical research agenda. The initiation and development of appropriate clinical studies requires a focus on devising suitable outcome measures, including a disease activity index, an optimal damage index, and a specific quality of life index.